Antifungal hydrogel bead as well as preparation method and application thereof
By loading DD/CD-MOF complex in hydrogel beads, the problem of chemical fungicide pollution in post-harvest disease prevention and control of citrus fruits is solved, and efficient and stable antifungal hydrogel beads are achieved, which significantly reduces the incidence of disease and quality deterioration of citrus fruits.
Patent Information
- Application Number
- CN202510633954.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-19
AI Technical Summary
In the prior art, post-harvest disease prevention and control of citrus fruits mainly relies on chemical fungicides, which poses complex operation and environmental pollution risks. In addition, volatile organic compounds such as 2,4-decadalene are volatile and unstable when used, which limits their industrial application in preservation of citrus fruits.
The cyclodextrin metal organic framework (CD-MOF) was prepared by ultrasonic assisted method, and the antifungal active substance 2,4-decadalene (DD) was loaded into CD-MOF to form a DD/CD-MOF complex, and it was encapsulated into the sodium alginate/egg egg white hydrogel bead system to prepare antifungal hydrogel beads DD/CD-MOF@AEW.
It improves the stability of DD and the crystallinity of hydrogel beads, enhances the ability to withstand external forces and dispersed stresses, achieves more efficient prevention and treatment and preservation effects of green mold in citrus fruits, and reduces the incidence of post-harvest disease and quality deterioration of fruits.
Smart Images

Figure CN120501146A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food preservation and relates to antifungal hydrogel beads and a preparation method and application thereof. Background Art
[0002] Citrus is one of my country's important economic crops, with a large planting area and high yield. Currently, its fruit is mainly consumed fresh. However, citrus fruits are extremely susceptible to invasion by pathogens during post-harvest circulation, causing post-harvest diseases. Among them, green mold disease caused by infection with Penicillium digitatum is particularly serious, causing rot rates of up to 90% in citrus fruits, resulting in huge economic losses. Currently, the prevention and control of post-harvest diseases of citrus fruits still mainly relies on immersion treatment with chemical fungicides. This method is not only complex to operate, but also may cause environmental pollution problems and even pose a potential threat to human health. Therefore, the development of an efficient, safe, and easy-to-use green mold disease prevention and control technology has become an urgent problem to be solved in the field of citrus post-harvest preservation.
[0003] In recent years, microbial volatile organic compounds (VOCs) have attracted considerable research attention due to their significant antifungal activity. Antimicrobial VOCs produced by microorganisms such as yeast, bacteria, and fungi have become a research hotspot. The Kluyveromyces marxianus S3A2 strain secretes 2,4-decadienal (DD), a volatile organic compound with potent antifungal activity. However, DD is highly volatile and sensitive to light, heat, and oxygen, making it prone to explosive release during practical application. This not only reduces its efficacy and utilization, but also severely limits its industrial application.
[0004] Hydrogel beads are spherical hydrogel systems with an internal three-dimensional network structure. Due to their small mass and volume, compact internal structure, and high stability, they have shown great potential in encapsulating and protecting bioactive substances in recent years. In an earlier study, the inventors prepared a green and safe antifungal hydrogel bead DD@AEW using sodium alginate (SA) and egg white (EW) as the matrix and DD as the antifungal agent. They found that when the ratio of SA to EW was 2:1, the encapsulation efficiency of DD in the hydrogel beads AEW2:1 was the highest. Hydrogel beads DD1@AEW2:1 with the addition of 1% DD could inhibit the growth of Penicillium digitatum, a common pathogen of citrus fruit, in a non-contact manner, effectively reducing the incidence of citrus diseases (Feiyue Peng, et al. Preparation and characterization of 2,4-decadienal-loaded sodiumalginate / egg white hydrogel beads and its application in green mold control of citrus. International Journal of Biological Macromolecules, Volume 304, Part 1, April 2025, 140708). Summary of the Invention
[0005] The purpose of the present invention is to further conduct in-depth research based on earlier studies and provide a new type of antifungal hydrogel beads with better stability, better prevention and control of post-harvest diseases of citrus fruits, and better control of the logistics, preservation and storage quality of citrus fruits.
[0006] After research, the present invention provides the following technical solutions:
[0007] 1. A method for preparing antifungal hydrogel beads, comprising the following steps:
[0008] 1) Preparation of cyclodextrin metal-organic framework (CD-MOF)
[0009] γ-cyclodextrin (γ-CD), potassium hydroxide and water were mixed and filtered through a microporous membrane. Methanol was added to the filtrate and heated in a water bath until a clear and transparent solution was obtained. Polyethylene glycol-20000 was added to the solution and ultrasonicated. The solution was allowed to stand and the supernatant was discarded. The resulting precipitate was washed and dried to obtain CD-MOF powder.
[0010] 2) Preparation of DD-loaded cyclodextrin metal-organic framework (DD / CD-MOF)
[0011] Dissolve DD in anhydrous ethanol to prepare a DD solution, mix it with the CD-MOF powder prepared in step 1), stir, and centrifuge. The resulting precipitate is washed and dried to obtain DD / CD-MOF powder;
[0012] 3) Preparation of antifungal hydrogel beads (DD / CD-MOF@AEW)
[0013] SA and emulsifier Tween 80 were dissolved in water to prepare SA solution, which was mixed with EW. The DD / CD-MOF powder prepared in step 2) was added and homogenized to obtain an emulsion. The emulsion was then dropped into a calcium chloride solution and cross-linked to form hydrogel beads. The solution was filtered, washed with water, and dried to obtain hydrogel beads DD / CD-MOF@AEW.
[0014] Furthermore, in step 1), the ratio of γ-CD, potassium hydroxide, water, and methanol is 162 mg:56 mg:5 mL:3 mL, and the amount of polyethylene glycol-20000 is to add polyethylene glycol-20000 to the solution to a final concentration of 8 mg / mL.
[0015] Furthermore, in step 1), the ultrasonic power is 500 W and the ultrasonic time is 10 min.
[0016] Furthermore, the step 2) is to dissolve DD in anhydrous ethanol to prepare a concentration of 1 mg·mL -1 The DD solution is mixed with the CD-MOF powder prepared in step 1), wherein the molar ratio of γ-CD to DD in the CD-MOF is 1:8.
[0017] The “molar ratio of γ-CD to DD in CD-MOF” refers to calculating the molar mass of CD-MOF according to the molar mass of γ-CD and then calculating the molar ratio with DD.
[0018] Furthermore, the step 2) is stirring at room temperature for 3 hours.
[0019] Furthermore, in step 3), SA and emulsifier Tween 80 are dissolved in water to prepare a solution with an SA concentration of 2% (g / mL) and a Tween 80 concentration of 1% (g / mL), which is mixed with EW at a volume ratio of 2:1, and the DD / CD-MOF powder prepared in step 2) is added to make the final concentration of DD 1% (mg / mL). The emulsion is homogenized and dropped into a calcium chloride solution with a concentration of 1% (g / mL). Hydrogel beads are cross-linked to form hydrogel beads, which are filtered and washed with water to obtain hydrogel beads DD / CD-MOF@AEW.
[0020] 2. Antifungal hydrogel beads prepared using the above preparation method.
[0021] 3. Application of the antifungal hydrogel beads in the preparation of citrus fruit fresh-keeping materials.
[0022] Furthermore, the citrus fruit fresh-keeping material can not only prevent and treat citrus fruit post-harvest diseases, but also maintain the quality of citrus fruit during logistics, transportation and storage.
[0023] Furthermore, the post-harvest disease of citrus fruit is citrus green mold.
[0024] The beneficial effects of the present invention are as follows: the present invention first prepares CD-MOF by an ultrasound-assisted method, then uses an impregnation method to encapsulate the volatile compound DD with antifungal activity in CD-MOF to prepare a DD-loaded CD-MOF composite (DD / CD-MOF), and finally loads DD / CD-MOF into a SA / EW hydrogel bead system to prepare DD / CD-MOF-loaded SA / EW hydrogel beads (DD / CD-MOF@AEW).
[0025] CD-MOF encapsulation significantly improved the stability of DD; the introduction of DD also significantly enhanced the stability of CD-MOF in the hydrogel system. The DD-loaded CD-MOF complex altered the crystallization behavior of the SA / EW hydrogel beads, increasing their crystallinity and making the hydrogel beads DD / CD-MOF@AEW more resistant to external forces and dispersion stress. The tighter molecular arrangement in the crystalline region also imparted improved thermal and chemical stability to the hydrogel beads DD / CD-MOF@AEW. Materials with high crystallinity have a more regular pore structure, which helps improve the encapsulation efficiency of active molecules. Active molecules can be more evenly distributed in the ordered pores, resulting in higher loadings and potentially more stable and controllable release of active molecules.
[0026] The hydrogel beads DD / CD-MOF@AEW obtained in this invention exhibit highly effective antibacterial properties against the pathogenic fungus Penicillium digitatum. They can significantly reduce the incidence of postharvest green mold in citrus fruit, delay fruit quality deterioration, and effectively preserve citrus fruit after simulated transport vibration. Compared to the hydrogel beads DD1@AEW2:1 produced by the inventors in their earlier research, the hydrogel beads DD / CD-MOF@AEW in this invention are more effective in controlling postharvest green mold in citrus fruit and maintaining the freshness of citrus fruit after simulated transport vibration. This provides an efficient, environmentally friendly, and sustainable solution for citrus fruit logistics preservation and storage quality control. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The effects of different ultrasonic powers and different ultrasonic times on the micromorphology and particle size of CD-MOF.
[0028] Figure 2 The effects of the molar ratio of γ-CD to DD in CD-MOF and stirring time on the encapsulation of DD by CD-MOF.
[0029] Figure 3Scanning electron microscope (SEM) images of CD-MOF and DD / CD-MOF.
[0030] Figure 4 Fourier transform infrared (FT-IR) spectra of γ-CD, CD-MOF and DD / CD-MOF.
[0031] Figure 5 X-ray diffraction (XRD) patterns of γ-CD, CD-MOF and DD / CD-MOF.
[0032] Figure 6 Thermogravimetric analysis (TGA) curves of CD-MOF and DD / CD-MOF.
[0033] Figure 7 Field emission scanning electron microscopy (FE-SEM) images of the surface and cross-section of CD-MOF@AEW and DD / CD-MOF@AEW.
[0034] Figure 8 FT-IR images of AEW, CD-MOF@AEW and DD / CD-MOF@AEW.
[0035] Figure 9 XRD patterns of CD-MOF@AEW and DD / CD-MOF@AEW.
[0036] Figure 10 TGA curves of CD-MOF@AEW and DD / CD-MOF@AEW.
[0037] Figure 11 Figure 3 Control effects of DD, AEW, DD1@AEW2:1, and DD / CD-MOF@AEW on postharvest green mold disease in citrus fruits: (a) disease incidence in each group on the 6th day after inoculation; (b) disease incidence in each group on the 4th and 6th days of storage; (c) lesion diameter in each group on the 4th and 6th days of storage.
[0038] Figure 12 Citrus fruits were treated with simulated transport vibration: (a) Citrus fruits were packed in boxes and subjected to simulated transport vibration; (b) control group; (c) DD combined with simulated transport vibration group; (d) hydrogel beads (AEW, DD1@AEW2:1, DD / CD-MOF@AEW) combined with simulated transport vibration group.
[0039] Figure 13 Effects of DD1@AEW2:1 and DD / CD-MOF@AEW on the decay rate of citrus fruit after simulated transportation vibration.
[0040] Figure 14Effects of DD1@AEW2:1 and DD / CD-MOF@AEW on the weight loss rate of citrus fruit after simulated transportation vibration.
[0041] Figure 15 Effects of DD1@AEW2:1 and DD / CD-MOF@AEW on the firmness of citrus fruit after simulated transportation vibration.
[0042] Figure 16 Effects of DD1@AEW2:1 and DD / CD-MOF@AEW on the soluble solids content of citrus fruit after simulated transportation vibration.
[0043] Figure 3 、 Figures 12 to 16 Different lowercase letters within the same group indicate significant differences (p<0.05), and the vertical lines represent the standard error of the mean. DETAILED DESCRIPTION
[0044] In order to make the objectives, technical solutions and beneficial effects of the present invention more clear, preferred embodiments of the present invention are described in detail below.
[0045] Example 1 Preparation of antifungal hydrogel beads DD / CD-MOF@AEW
[0046] Preparation of 1CD-MOF
[0047] 1.1 Ultrasonic-assisted preparation of CD-MOF
[0048] CD-MOF was prepared using an ultrasound-assisted method. The steps are as follows: 324 mg of γ-CD, 112 mg of potassium hydroxide, and 10 mL of deionized water were thoroughly mixed at room temperature and filtered through a 0.45 μm microporous filter. 6 mL of methanol was added to the filtrate to form a milky white suspension. This suspension was then placed in a 50°C water bath until a clear, transparent solution was obtained. 128 mg of polyethylene glycol-20000 was added to the resulting solution, and the solution was immediately sonicated (ultrasonic powers of 200, 300, 400, 500, and 600 W, for 3, 5, 10, and 15 minutes, respectively). The solution was then allowed to stand for 2 hours, and the supernatant was discarded. The resulting precipitate was washed three times with methanol and dried at 50°C for 24 hours to obtain the CD-MOF product.
[0049] 1.2 Preparation process optimization
[0050] In the synthesis and application of metal-organic framework (MOF) materials, crystal size and particle morphology are important parameters that influence their performance and application. MOF materials are prepared using ultrasound-assisted methods. The primary effect of ultrasound is the continuous formation and collapse of cavitation bubbles within the solution. These bubbles cause severe disturbances within the solution. Therefore, ultrasound can control the rates of nucleation and crystal growth, thereby controlling the ultimate size of each particle.
[0051] To explore the optimal conditions for ultrasound-assisted preparation of CD-MOF, we investigated the effects of different ultrasonic powers (200, 300, 400, 500, and 600 W) and ultrasonic times (3, 5, 10, and 15 minutes) on the micromorphology of CD-MOF. CD-MOF samples prepared under different preparation conditions were characterized using SEM, and their particle sizes were measured.
[0052] The results are as follows Figure 1 As shown. With the change of ultrasonic power and ultrasonic time, the shape of CD-MOF gradually changes from irregular to uniform crystal structure, and the particle size is all in the micron level. In the power range of 200-400W, with the increase of ultrasonic power, the particle size of CD-MOF shows a significant decreasing trend. This phenomenon is attributed to the ultrasonic-assisted anti-solvent crystallization mechanism. A moderate increase in ultrasonic power can reduce the width of the metastable zone of the solution and promote the rapid establishment of supersaturation, which is conducive to the formation of crystals with smaller particle sizes. However, when the ultrasonic power exceeds 500W, the local high temperature and high pressure generated by the cavitation effect significantly increase the density of nucleation sites, resulting in restricted crystal growth and ultimately the formation of smaller particles. This finding is consistent with the mechanism of the influence of ultrasonic cavitation effect on crystal nucleation reported in the literature. The particle size of CD-MOF gradually increases with the increase of ultrasonic time (3-10min) and reaches a maximum value at 10min. This phenomenon may be due to the energy provided by ultrasonic treatment, which causes increased crystal nucleation and accelerates the aggregation reaction, resulting in the formation of larger aggregates within the duration. However, when the time was further increased (15 min), the particle size of CD-MOF decreased instead. This may be because the collisions between particles increased due to the long time, and the excessive energy caused the structure to be destroyed, resulting in some irregularly shaped particles, which reduced the particle size.
[0053] Based on these results and by comparing the morphology and particle size distribution of CD-MOFs prepared under different preparation conditions, the optimal process conditions were determined to be: ultrasonic power of 500 W and ultrasonic time of 10 minutes. The CD-MOFs prepared under these conditions exhibited a regular cubic morphology, uniform particle size distribution, and good dispersion.
[0054] 2. Preparation of DD / CD-MOF
[0055] 2.1 Preparation of DD / CD-MOF by impregnation method
[0056] DD / CD-MOF was prepared by impregnation method. The specific steps are as follows: DD was dissolved in anhydrous ethanol to a concentration of 1 mg·mL -1 Accurately weigh CD-MOF powder and mix the DD solution with the CD-MOF powder in a specific ratio (the molar ratio of γ-CD to DD in CD-MOF is 4:1, 1:1, 1:4, 1:8, 1:16, and 1:32, respectively). Stir at room temperature for 1, 3, 6, and 12 hours, respectively. After stirring, centrifuge at 4000 rpm and collect the supernatant and precipitate. Wash the precipitate three times with anhydrous methanol and freeze-dry for 24 hours to obtain the DD / CD-MOF product.
[0057] 2.2 Preparation process optimization
[0058] In order to optimize the impregnation preparation process of DD / CD-MOF, the encapsulation efficiency was used as the key evaluation index, and the important process conditions (molar ratio of γ-CD to DD in CD-MOF and stirring time) were screened.
[0059] The supernatant collected in "2.1 Preparation of DD / CD-MOF by Immersion Method" was diluted and the absorbance value was measured with a microplate reader. The DD content was obtained by the standard curve and the encapsulation efficiency was calculated according to the following formula: Encapsulation efficiency (%) = M DD / CD-MOF / M DD ×100, where M DD / CD-MOF is the amount of DD encapsulated in DD / CD-MOF, M DD is the initial addition amount of DD.
[0060] The results are as follows Figure 2As shown. The encapsulation efficiency shows a trend of first increasing and then decreasing with increasing stirring time. When the stirring time is 1h, the encapsulation efficiency is relatively low; when the stirring time increases to 3h, the encapsulation efficiency reaches a maximum value (33.18%±2.46%); then, as the stirring time further increases, the encapsulation efficiency gradually decreases. Sufficient stirring time can effectively increase the collision between DD and CD-MOF, and encapsulation requires a certain amount of time to complete. Therefore, appropriately increasing the stirring time is beneficial to improving the encapsulation efficiency of CD-MOF for DD. However, the encapsulation capacity of CD-MOF is limited, and the encapsulation efficiency will tend to stabilize after a certain stirring time. On the other hand, when the molar ratio of γ-CD to DD in CD-MOF is adjusted from 4:1 to 1:8, the encapsulation efficiency shows a significant upward trend, but when the molar ratio of the two is adjusted from 1:8 to 1:32, the encapsulation efficiency shows a gradual downward trend. This is because when the amount of DD is small, there are enough cavities in the CD-MOF channels to adsorb DD, so the encapsulation efficiency gradually increases. However, as the amount of DD increases, the cavities in the CD-MOF channels are gradually occupied by DD until saturation, and excess DD can no longer enter the CD-MOF channels, resulting in a decrease in encapsulation efficiency.
[0061] Based on the above results and taking into account the production efficiency, the optimal process conditions were determined as follows: the molar ratio of γ-CD to DD in CD-MOF was 1:8 and the stirring time was 3 h.
[0062] 3. Characterization of CD-MOF and DD / CD-MOF
[0063] The products CD-MOF and DD / CD-MOF were analyzed by SEM, FT-IR, XRD and TGA, respectively.
[0064] SEM images of CD-MOF and DD / CD-MOF are shown in Figure 2. Figure 3 Before DD loading, CD-MOF exhibited a highly regular cubic morphology with a smooth surface and uniform particle size distribution. After DD loading, DD / CD-MOF maintained its cubic shape, but the edges became blurred, the crystal surface became rough, and small clusters were observed adhering to the crystal surface, likely due to DD attachment.
[0065] FT-IR images of γ-CD, CD-MOF and DD / CD-MOF are shown in Figure 2. Figure 4 The characteristic functional group peaks of CD-MOF mainly include 862, 1362, 1644 and 3299 cm -1 etc., among which 3400-3000cm -1 Caused by -OH stretching vibration; 2900-3000cm -1 Caused by CH stretching vibration; 1644cm -1It may be related to C=O stretching vibration; 1362, 862cm -1 Caused by CO stretching vibration. The peak positions of CD-MOF and γ-CD are highly consistent, indicating that the prepared CD-MOF still retains the structure of γ-CD. Compared with γ-CD, the peak positions and peak widths of -OH stretching vibration peak, C=O and CO stretching vibration of CD-MOF have changed, which may be due to hydrogen bond interaction and K + caused by coordination interference.
[0066] The XRD patterns of γ-CD, CD-MOF and DD / CD-MOF are shown in Figure 2. Figure 5 As shown in the figure. Compared with γ-CD, CD-MOF has many different diffraction peaks, with characteristic diffraction peaks appearing at 4°, 6.9°, 13.4°, and 16.7°. The diffraction patterns of CD-MOF and DD / CD-MOF are basically consistent, and the positions and intensities of the main characteristic diffraction peaks do not change significantly, indicating that they have the same crystal structure. From this, it can be inferred that DD mainly exists in an amorphous state within the cavity of CD-MOF, forming a stable host-guest complex with the main framework through hydrogen bonding. This loading method not only maintains the crystal structure of CD-MOF, but also ensures the effective encapsulation of active substances.
[0067] The TGA curves of CD-MOF and DD / CD-MOF are shown in Figure 2. Figure 6 The mass loss of both materials can be divided into two main stages: the first stage, which occurs in the temperature range of 25°C-95°C, is mainly caused by the evaporation of water molecules and methanol in the materials; the second stage, which occurs between 215°C and 400°C, shows significant weight loss, corresponding to the degradation of the CD-MOF crystal structure and the volatilization of DD. Interestingly, the degradation of DD occurs after 280°C, indicating that CD-MOF effectively improves the stability of DD and delays its degradation, thereby protecting it from environmental changes. The final results show that the weight loss of DD / CD-MOF is higher than that of CD-MOF, further confirming the successful loading of DD into CD-MOF.
[0068] 4. Preparation of DD / CD-MOF@AEW
[0069] 2g of SA powder and Tween 80 at a final concentration of 1% (g / mL) were added to 100mL of deionized water and stirred continuously at room temperature until completely dissolved. Residual bubbles in the solution were removed by sonication to obtain a SA solution. The resulting SA solution was mixed with EW at a volume ratio of 2:1. DD / CD-MOF powder was then added to a final DD concentration of 1% (mg / mL) (calculated based on a 33.18% encapsulation efficiency of DD / CD-MOF for DD, with the added weight of approximately 1.16g of DD / CD-MOF powder). The mixture was homogenized at 8000rpm / min for 2 minutes in the dark. The resulting emulsion was added dropwise at a constant rate to a 1% (g / mL) calcium chloride solution using a 10mL syringe (0.7mm inner diameter). The mixture was crosslinked for 40 minutes in the dark with stirring to form hydrogel beads. The hydrogel beads were filtered through a mesh, washed three times with deionized water, and any residual surface moisture was removed with filter paper. The mixture was then freeze-dried for 24 hours to obtain DD / CD-MOF@AEW hydrogel beads.
[0070] At the same time, according to the above method, CD-MOF was used instead of DD / CD-MOF to prepare the control CD-MOF@AEW (cyclodextrin metal organic framework hydrogel beads); according to the above method, after the obtained SA solution and EW were mixed in a volume ratio of 2:1, DD / CD-MOF was not added to prepare the control AEW (sodium alginate / egg white hydrogel beads).
[0071] 5. Characterization of DD / CD-MOF@AEW
[0072] The products CD-MOF@AEW and DD / CD-MOF@AEW were analyzed by FE-SEM, FT-IR, XRD and TGA, respectively.
[0073] FE-SEM images of the surface and cross section of CD-MOF@AEW and DD / CD-MOF@AEW are shown in Figure 4. Figure 7 As shown. The appearance of CD-MOF@AEW is spherical with a relatively rough surface; the interior is a tight multi-layered lamellar structure, and no cubic structure is observed. This may be because CD-MOF disintegrates when exposed to water, which affects its morphology. The appearance of DD / CD-MOF@AEW is similar to that of CD-MOF@AEW, but it presents a "core-shell" structure with tighter edges and a looser interior. Surprisingly, many cubic particles were observed inside, and it is speculated that these cubes are DD / CD-MOF. They can be stably loaded in the hydrogel system, and their morphology is not affected by moisture. This result shows that the introduction of DD significantly improves the stability of CD-MOF in the hydrogel system and retains the cubic structure.
[0074] FT-IR images of AEW, CD-MOF@AEW and DD / CD-MOF@AEW are shown in the figure below. Figure 8 The infrared spectrum of CD-MOF@AEW shows the characteristic peaks of AEW, while some characteristic peaks of CD-MOF (such as 3280, 1027, 940 cm -1 Compared with AEW, the -OH stretching vibration peak of CD-MOF@AEW at 3280 cm-1 is weakened, which may be the result of hydrogen bonding interaction. The characteristic peak position of DD / CD-MOF@AEW is similar to that of CD-MOF@AEW, in which the characteristic peak of DD at 1158 cm-1 appears. -1 , indicating successful DD loading. Analysis of the DD / CD-MOF@AEW spectrum revealed that its characteristic absorption peaks were a superposition of the existing characteristic peaks of each component, with no new chemical bond vibration peaks appearing. This phenomenon confirms that only physical interaction exists between DD / CD-MOF and the AEW matrix, with no chemical bond formation or breaking occurring.
[0075] The XRD patterns of CD-MOF@AEW and DD / CD-MOF@AEW are shown in Figure 2. Figure 9 Compared to CD-MOF@AEW, DD / CD-MOF@AEW exhibits sharper diffraction peaks, more crystalline regions, more regular molecular arrangement, and significantly improved crystallinity. This suggests that the DD-loaded CD-MOF alters the crystallization behavior of the hydrogel beads, making them more resistant to external forces and dispersed stress. Furthermore, materials with high crystallinity typically have more regular pore structures, which helps improve the encapsulation efficiency of active substances. Active molecules can be more evenly distributed in the ordered pores, resulting in a higher loading capacity and potentially more stable and controllable release of active substances. Due to the denser molecular arrangement in the crystalline regions, the material exhibits better thermal and chemical stability. In CD-MOF@AEW, only some of the characteristic diffraction peaks belonging to CD-MOF (7.6, 16.9°) are retained and slightly shifted, which may be due to a slight change in the crystal plane spacing and arrangement. DD / CD-MOF@AEW retains more characteristic diffraction peaks belonging to CD-MOF (5.4, 7.5, 16.8°), indicating that the CD-MOF structure is more retained. This result is consistent with the results of micromorphology and infrared spectroscopy analysis.
[0076] The TGA curves of CD-MOF@AEW and DD / CD-MOF@AEW are shown in Figure 2. Figure 10As shown. Their mass loss can be divided into two stages. The temperature range of the first stage is 25℃-150℃, which is mainly due to water evaporation; the second stage occurs at 255℃-430℃, which is mainly due to the thermal decomposition of the hydrogel matrix and γ-CD and the volatilization of DD. CD-MOF@AEW and DD / CD-MOF@AEW have similar thermal degradation patterns. At the end of degradation (around 600℃), they have a mass difference of 4.5%, which may be caused by the thermal decomposition loss of the loaded DD.
[0077] Example 2 Determination of the in vitro antibacterial activity of antifungal hydrogel beads DD / CD-MOF@AEW against P. digitatum
[0078] The in vitro antifungal properties of DD / CD-MOF@AEW were evaluated by fumigation method and compared with those of DD1@AEW2:1 hydrogel beads prepared earlier (Feiyue Peng, et al. Preparation and characterization of 2,4-decadienal-loaded sodiumalginate / egg white hydrogel beads and its application in green mold control of citrus. International Journal of Biological Macromolecules, Volume 304, Part 1, April 2025, 140708).
[0079] The pathogenic fungus Penicillium digitatum used in the experiment was isolated from naturally diseased citrus fruits in an orchard and stored at -80°C. Before the experiment, the stored strain was thawed at room temperature, inoculated onto potato dextrose agar (PDA) medium, and activated at 25°C for 6 days. The culture was rinsed with sterile water, filtered through gauze to obtain a spore suspension, and diluted with sterile water to 1×10 5 spores·mL -1 10 μL of Penicillium digitatum spore suspension (1×10 5 spores·mL -1) were dropped in the center of the PDA plate and dried naturally; AEW, DD1@AEW2:1, and DD / CD-MOF@AEW that had been irradiated with ultraviolet light for 30 minutes (turned over once every 10 minutes) were placed in the center of the culture dish lid, corresponding to the AEW group, DD1@AEW2:1 group, and DD / CD-MOF@AEW group, respectively. A control group without anything was also set up; finally, the culture dish was sealed with a sealing film and cultured in a constant temperature incubator at 25°C. The growth diameter of the P. digitatum colony on the culture medium was measured from day 2 to day 6.
[0080] The results are shown in Table 1. On day 6 of culture, the colony diameters of the control and AEW groups were (65.28±1.26) mm and (61.83±0.27) mm, respectively, indicating that AEW had no significant inhibitory effect on the growth of P. digitatum. In contrast, both the DD / CD-MOF@AEW and DD1@AEW2:1 groups exhibited significant inhibitory effects on P. digitatum, with no observed colony growth and an inhibition rate of 100%, demonstrating excellent antifungal properties.
[0081] Table 1 P. digitatum colony diameters in each treatment group (mm)
[0082] time control group AEW Group DD1@AEW2:1 group DD / CD-MOF@AEW group Day 2 <![CDATA[19.83±0.16 b ]]> <![CDATA[20.92±0.12 a ]]> - - Day 3 <![CDATA[33.56±0.08 a ]]> <![CDATA[33.71±0.29 a ]]> - - Day 4 <![CDATA[44.61±1.02 b ]]> <![CDATA[45.89±0.34 a ]]> - - Day 5 <![CDATA[55.78±1.37 a ]]> <![CDATA[50.00±1.30 b ]]> - - Day 6 <![CDATA[65.28±1.26 a ]]> <![CDATA[61.83±0.27 b ]]> - -
[0083] Note: Different lowercase letters in the same group indicate significant differences (p<0.05), and “-” indicates no colony growth was observed.
[0084] Example 3 Control effect of antifungal hydrogel beads DD / CD-MOF@AEW on postharvest green mold disease in citrus fruits
[0085] Citrus fruits (Citrus sinensis, L. Osbeck cv. Jincheng 447#) were sourced from Beibei District, Chongqing. Healthy fruits of uniform size, similar maturity, and free of mechanical damage and disease infection were selected as experimental materials. The fruits were first disinfected by soaking in a 2% sodium hypochlorite solution for 2 minutes, then rinsed with water and allowed to dry naturally. The surface of the fruit was then wiped and disinfected with a 75% ethanol solution. Two symmetrical circular wounds were created in the equatorial region of the citrus peel using a sterile punch. Each wound was inoculated with 1 × 10 4 spores·mL -1The citrus fruits were randomly divided into five groups after inoculation: control, DD, AEW, DD1@AEW2:1, and DD / CD-MOF@AEW. In the DD group, DD was dripped onto filter paper, which was then placed in a culture dish. In the AEW, DD1@AEW2:1, and DD / CD-MOF@AEW groups, the corresponding hydrogel beads were placed directly in a culture dish. The culture dishes and citrus fruits were then sealed in a sealed plastic box in the last four groups, while the citrus fruits were only sealed in a sealed plastic box in the control group. The plastic boxes in each group were then stored at 25°C and a relative humidity of 80-85%. The plastic boxes were opened on the 4th and 6th days, and the incidence rate and lesion diameter of the citrus fruits were observed and recorded. Six citrus fruits were placed in each plastic box as a replicate, and three replicates were set up for each group at each time point (4th and 6th days).
[0086] The results are as follows Figure 11 As shown in the figure. On the 6th day of storage, the fruits in the control, DD, and AEW groups all showed relatively severe rot symptoms. However, compared with the control group, the morbidity of the DD1@AEW2:1 and DD / CD-MOF@AEW groups decreased by 11.1% and 27.78%, respectively, on the 4th day of storage, and by 24.13% and 27.59%, respectively, on the 6th day of storage. The lesion diameters also decreased by 29.67% and 36.62%, respectively. This indicates that both DD1@AEW2:1 and DD / CD-MOF@AEW can effectively inhibit the occurrence of postharvest green mold in citrus fruits, and the latter has a better control effect than the former.
[0087] Example 4: Preservation effect of antifungal hydrogel beads DD / CD-MOF@AEW on citrus fruits after simulated transport vibration
[0088] In order to investigate the effect of DD / CD-MOF@AEW on reducing the loss of citrus fruits during post-harvest logistics transportation, the present invention conducted a citrus fruit simulated transportation vibration experiment (such as Figure 12 shown).
[0089] The citrus fruits were randomly divided into 6 groups: (1) control group: the citrus fruits were placed in a courier box; (2) simulated transport vibration (STV) group: the citrus fruits were placed in a courier box and placed on a vibration table for fixed-frequency vibration treatment; (3) AEW combined with simulated transport vibration (AEW+STV) group: the citrus fruits were placed in a courier box, a breathable box carrying AEW was attached to the top of the courier box, and the citrus fruits were placed on a vibration table for fixed-frequency vibration treatment; (4) DD combined with simulated transport vibration (DD+STV) group: the citrus fruits were placed in a courier box, DD was dripped on filter paper, and the filter paper was attached to the top of the courier box, and the citrus fruits were placed on a vibration table for fixed-frequency vibration treatment. The fixed-frequency vibration treatment was carried out on the vibration table; (5) DD1@AEW2:1 combined with simulated transport vibration (DD1@AEW2:1+STV) group: citrus fruits were placed in a courier box, and a breathable box carrying DD1@AEW2:1 was attached to the top of the courier box, and the courier box was placed on a vibration table for fixed-frequency vibration treatment; (6) DD / CD-MOF@AEW combined with simulated transport vibration (DD / CD-MOF@AEW+STV) group: citrus fruits were placed in a courier box, and a breathable box carrying DD / CD-MOF@AEW was attached to the top of the courier box, and the courier box was placed on a vibration table for fixed-frequency vibration treatment. Each courier box (SF Express No. 3 corrugated cardboard box, size 30×25×20cm) 3 , maximum load 5kg), 24 citrus fruits were placed in a box as a replicate, with three replicates set up in each group. The fixed-frequency vibration treatment had a vibration frequency of 16 Hz and a vibration time of 20 minutes. After the fixed-frequency vibration treatment, the express box was stored at 25°C and a relative humidity of 80-85%. The following fruit-related indicators were measured on the 5th, 10th, 15th, 20th, 25th, and 35th days of storage.
[0090] (1) Decay rate
[0091] Observe the fruit surface for signs of softening, lesions, or white mycelium. If present, record the fruit as rotten. Record the number of rotten fruits and calculate the rot rate.
[0092] The decay rate is the most intuitive and important indicator for evaluating the quality and shelf life of fruits after harvest. Figure 13The STV group had a significantly higher decay rate than the other treatments throughout the storage period (p < 0.05), indicating that vibration-treated citrus fruits are more susceptible to decay during storage. This may be because the collision between the fruit and the box walls during vibration causes mechanical damage, providing a pathway for pathogens to enter and accelerate the decay process. On the fifth day of storage, no decay was observed in the control group or the DD / CD-MOF@AEW group. Subsequently, as storage time increased, the decay rate of the citrus fruits in all treatment groups increased. On day 35 of storage, the decay rates of the control, STV, AEW+STV, DD+STV, DD1@AEW2:1, and DD / CD-MOF@AEW groups were 25%, 32.14%, 23.81%, 22.62%, 20.24%, and 16.67%, respectively. The decay rates of the DD1@AEW2:1 and DD / CD-MOF@AEW groups were 37.03% and 48.13% lower than those of the STV group, respectively, indicating that the latter group exhibited significantly better preservation than the former. Furthermore, the experimental results from the DD+STV, DD1@AEW2:1, and DD / CD-MOF@AEW groups further demonstrated that DD, as an antimicrobial agent, can effectively control postharvest diseases in citrus fruit. However, encapsulating DD in a slow-release carrier improves its storage stability and ensures its sustainable use, resulting in even greater antibacterial efficacy. In addition, the experimental results of the STV group and the AEW+STV group showed that AEW also had a certain disease control effect. This may be because its base material is composed of natural polysaccharides and proteins, which can absorb a small amount of pathogens in the air, thereby reducing the incidence of citrus fruits.
[0093] (2) Weight loss rate
[0094] Twelve fruits were randomly selected from each group and marked. They were weighed regularly using a precision electronic balance (accuracy 0.01 g) to calculate the weight loss rate of citrus fruits during storage.
[0095] Citrus fruit weight loss during storage is primarily due to two physiological processes: transpiration through the stomata and lenticels of the skin, leading to water evaporation; and respiratory metabolism, leading to the consumption of organic matter. These processes are key indicators for assessing the postharvest quality and storage stability of citrus fruit, providing a direct reflection of the fruit's freshness and water retention capacity. Adequate water maintains the firmness of citrus tissue, giving it a fresh, plump appearance. Excessive water loss softens the flesh, resulting in a poor taste.
[0096] The results are as follows Figure 14As shown. The weight loss rate of citrus fruits in all treatment groups continued to increase with the extension of storage time. Among them, the STV group showed the largest weight loss at each measurement time point, followed by the control group. Their weight loss rates reached 14.01% and 12.29% on the 35th day of storage (p<0.05). This phenomenon shows that mechanical vibration during logistics transportation will destroy the fruit skin structure, aggravate water loss, lead to a significant increase in weight loss rate, and thus accelerate the deterioration of fruit quality. The weight loss rates of all other treatment groups were lower than those of the STV group and the control group, indicating that AEW, DD, DD1@AEW2:1 and DD / CD-MOF@AEW can effectively delay the weight loss of citrus fruits caused by water loss, among which DD / CD-MOF@AEW has a better effect.
[0097] (3) Hardness
[0098] Twelve fruits were randomly selected from each group, and four test points were equidistantly selected around the fruit's equator. Citrus peel firmness was measured using an FTA fruit texture analyzer. The test parameters were: a P / 5 probe (5 mm diameter), a test speed of 10 mm / s, and a penetration depth of 1 mm.
[0099] Hardness is one of the important indicators for evaluating the post-harvest quality of fruits. It is affected by multiple factors, including the production of reactive oxygen species, the degree of cell swelling, the structure and composition of cell wall polysaccharides, and a higher degree of oxidation and water loss.
[0100] The results are as follows Figure 15 As shown. The hardness of citrus fruits in each treatment group showed a decreasing trend to varying degrees with the extension of storage time. This change is closely related to the ripening and aging process of the fruit. In the first 20 days of storage, the STV group showed the fastest rate of hardness decline compared with other groups, decreasing from 0.436 kg to 0.235 kg. This phenomenon indicates that mechanical vibration during logistics transportation will accelerate the degradation of the fruit cell wall structure and promote the dissolution of pectin substances, resulting in a rapid decrease in fruit hardness and accelerated softening process. On the 35th day of storage, the hardness of the fruit in the DD / CD-MOF@AEW group remained at 0.223 kg, which was significantly higher than that of the control group (p<0.05).
[0101] (4) Soluble solids content
[0102] Three fruits were randomly selected from each group. The pulp at the equator was taken after removing the peel. The pulp samples were obtained after juice extraction and gauze filtration. The soluble solids content was determined using a PAL-1 handheld sugar refractometer.
[0103] The soluble solids in fruit juice mainly include sugars, organic acids, vitamins, minerals and soluble pectin. Their content is an important indicator reflecting the maturity and quality of the fruit. The higher the soluble solids content, the higher the maturity of the fruit.
[0104] The results are as follows Figure 16 As shown in the figure, the soluble solids content of citrus fruit in the control, STV, and AEW+STV groups decreased slightly throughout storage, primarily due to the breakdown of soluble solids as respiratory substrates, providing energy for respiratory metabolic activity. The other three groups showed an upward trend, driven by the enzymatic hydrolysis of macromolecular polysaccharides into soluble sugars during storage. On the 35th day of storage, the soluble solids content of the DD / CD-MOF@AEW group reached 14.1%, significantly higher than that of the other treatments (p < 0.05), demonstrating improved preservation of the fruit's storage quality.
[0105] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing antifungal hydrogel beads, characterized in that: The following steps are involved: 1) Preparation of cyclodextrin metal-organic framework (CD-MOF) γ-cyclodextrin, potassium hydroxide and water were mixed and filtered through a microporous membrane. Methanol was added to the filtrate and heated in a water bath until a clear and transparent solution was obtained. Polyethylene glycol-20000 was added to the solution and ultrasonicated. The solution was allowed to stand and the supernatant was discarded. The resulting precipitate was washed and dried to obtain CD-MOF powder. 2) Preparation of 2,4-decadienal-loaded cyclodextrin metal-organic framework (DD / CD-MOF) Dissolving 2,4-decadienal in anhydrous ethanol to prepare a 2,4-decadienal solution, mixing the solution with the CD-MOF powder prepared in step 1), stirring, centrifuging, and washing and drying the resulting precipitate to obtain DD / CD-MOF powder; 3) Preparation of antifungal hydrogel beads, namely DD / CD-MOF@AEW Sodium alginate and Tween 80 were dissolved in water to prepare a sodium alginate solution, which was then mixed with egg white. The DD / CD-MOF powder prepared in step 2) was added and homogenized to obtain an emulsion. The emulsion was then added dropwise to a calcium chloride solution to cross-link and form hydrogel beads. The solution was filtered and washed with water to obtain hydrogel beads DD / CD-MOF@AEW.
2. The method for preparing antifungal hydrogel beads according to claim 1, wherein: In the step 1), the dosage ratio of γ-cyclodextrin, potassium hydroxide, water, and methanol is 162 mg:56 mg:5 mL:3 mL, and the dosage of polyethylene glycol-20000 is to add polyethylene glycol-20000 to the solution to a final concentration of 8 mg / mL.
3. The method for preparing antifungal hydrogel beads according to claim 2, wherein: In step 1), the ultrasonic power is 500 W and the ultrasonic time is 10 min.
4. The method for preparing antifungal hydrogel beads according to claim 1, wherein: The step 2) is to dissolve 2,4-decadienal in anhydrous ethanol to a concentration of 1 mg·mL -1 The 2,4-decadienal solution is mixed with the CD-MOF powder prepared in step 1), wherein the molar ratio of γ-cyclodextrin to 2,4-decadienal in the CD-MOF is 1:
8.
5. The method for preparing antifungal hydrogel beads according to claim 4, wherein: The step 2) is to stir at room temperature for 3 hours.
6. The method for preparing antifungal hydrogel beads according to claim 1, wherein: The step 3) is to dissolve sodium alginate and Tween 80 in water to prepare a solution with a sodium alginate concentration of 2% (g / mL) and a Tween 80 concentration of 1% (g / mL), mix it with egg white at a volume ratio of 2:1, add the DD / CD-MOF powder prepared in step 2) to make the final concentration of 2,4-decadienal 1% (mg / mL), homogenize to obtain an emulsion, drop it into a calcium chloride solution with a concentration of 1% (g / mL), cross-link to form hydrogel beads, filter, and wash with water to obtain hydrogel beads DD / CD-MOF@AEW.
7. Antifungal hydrogel beads prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the antifungal hydrogel beads according to claim 7 in preparing citrus fruit fresh-keeping materials.
9. The use according to claim 8, characterized in that: The citrus fruit fresh-keeping material can not only prevent and control citrus fruit post-harvest diseases, but also maintain the quality of the citrus fruit during logistics, transportation and storage.
10. The use according to claim 9, characterized in that: The post-harvest disease of citrus fruits is citrus green mold.